The Association of Urine Creatinine With Kidney Stone Prevalence in US Adults: Data From NHANES 2009–2018 - Shen, Xudong; Chen, Yan; Zhang, Yangyang; Xia, Kaiguo; Chen, Yang; Hao, Zongyao (Frontiers in Medicine, 2022)
Background: The primary objective of this project was to explore the association of urine creatinine (UCR) with the prevalence rate of kidney stones. Method: The National Health and Nutrition Examination Survey (NHANES) database was employed to conduct a cross-sectional study. The analysis samples included adults aged ≥20 years from five consecutive cycles of the NHANES 2009–2018. The association between UCR and kidney stones was detected using univariate analysis and multivariate logistic regression analysis. Further, subgroup analyses were performed to evaluate the subgroup effects. Results: After adjustment for all confounders, multiple logistic regression analysis revealed a weak positive relationship between UCR and kidney stone (OR = 1.015,95%CI:1.008–1.021). In the subgroup analysis stratified by sex, age, or race, the risk further increased in male (OR = 1.014,95%CI:1.005–1.023), female (OR = 1.015,95%CI:1.005–1.025), white race (OR = 1.022,95%CI:1.013–1.030), aged 40–59 years (OR = 1.017,95%CI:1.006–1.028), and aged 60–80 years (OR = 1.017,95%CI:1.006–1.028). Conclusions: Our results confirmed a moderately increased risk of kidney stone formation attributed to high levels of urine creatinine, especially in middle-aged and older adults and the white race.However,because of the cross-sectional design of the study, causal inferences cannot be made.